Konseptualisasi Siyāsah dalam Empat Mazhab Sunni: Perdebatan Yurisprudensial Klasik dan Logika Yuridis Fleksibilitas Politik - Muhammad Abu Dzar; Muntaha Artalim Zaim; Muhammad Amanullah (Institut Agama Islam Negeri Curup, 2026)
This article examines siyasah in classical Sunni fiqh as a form of jurisprudential reasoning, rather than as a theory of state institutions. This study employs a normative qualitative approach using comparative fiqh analysis and contextual jurisprudential interpretation to analyze authoritative classical fiqh texts from the Hanafi, Maliki, Shafi’i, and Hanbali schools pertaining to governance, political authority, public policy, and legal discretion. The comparative method is used to identify patterns of similarities and differences across schools in conceptualizing the relationship between law, political authority, and the public interest, while contextual interpretation is applied to situate fiqh arguments within their historical and methodological contexts. The research findings indicate that doctrinal differences regarding political discretion reflect the plurality of legal rationalities operating within a shared normative horizon, namely justice ('adl) and the public interest (maslahah). Political flexibility in this article is conceptualized as the juristic logic of political flexibility, namely an internally structured and ethically bound legal logic, not a value-free space of political power. This article concludes that siyasah syar'iyah is an integral form of bound discretion within the Islamic legal system, offering a historical, contextual-methodological, and non-reductionist framework for contemporary studies of Islamic law and politics.